Efficient management of benign laryngeal symptoms in an endoscopy outpatient clinic - Pia Järvenpää; Teemu Kinnari; Petra Pietarinen; Taru Ilmarinen (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objectives A globus and thick mucus in the throat are common reasons for referral to an ear, nose, and throat (ENT) specialist. ENT outpatient appointments focus on nasolaryngoscopy examinations, patient education, and reassurance. An endoscopic outpatient clinic (EOC) was established to efficiently manage patients with benign laryngeal symptoms. Methods Patients referred between February 2022 and June 2023 due to a globus and/or thick mucus in the throat were immediately contacted via post. The contact letter included patient education about the potential underlying reasons for their symptoms and self‐care instructions. A 15‐min outpatient visit was scheduled for an ENT examination and nasolaryngoscopy. Patients completed a questionnaire about their current symptoms and whether they had followed the self‐care instructions just before visiting the EOC and 1‐month following their appointment. Results In total, 203 patients examined in the EOC were included in the study. Before the EOC visit, most patients (89.2%) considered the information letter useful, it relieved concerns in 44.2% of patients, and 73.2% patients had already followed the self‐care instructions. After the 1‐month follow‐up period, symptoms diminished significantly (p < .001). Conclusions Instructions for self‐care and encouragement relieved concerns among patients with benign laryngeal symptoms. Moreover, symptoms improved significantly after a 1‐month follow‐up period. Level of evidence 4.